Clinical features, treatment and outcome in neurosarcoidosis: systematic review and meta-analysis - Fritz, Daan; van de Beek, Diederik; Brouwer, Matthijs C. (BMC neurology, 2016)
Background Neurosarcoidosis is a rare variant of sarcoidosis and is only described in small cohort studies. We define clinical features, treatment and outcome of patients with neurosarcoidosis over the last 35 years. Methods We performed a systematic review and meta-analysis of studies on neurosarcoidosis published between 1980 and 2016. Studies were included if they reported at least 5 cases. Studies describing one specific neurological presentation were excluded. Results We identified 29 articles describing 1088 patients diagnosed between 1965 and 2015. Neurosarcoidosis occurred in 5% of patients with systemic sarcoidosis. Mean age at presentation was 43 years and neurological symptoms were the first clinical manifestation of sarcoidosis in 52%. The most commonly reported feature of neurosarcoidosis was cranial neuropathy in 55%, with the facial and optic nerve most commonly affected, followed by headache in 32%. Pleiocytosis and elevated CSF protein were found in 58 and 63%. MRI of the brain showed abnormalities in 70%. Chest X-ray, chest CT, or gallium-67-scintigraphy showed findings consistent with sarcoidosis in 60%, 70% and 69%, respectively. First line therapy with corticosteroids was initiated in 434 of 539 patients (81%). Second and third line therapy was started in 27 and 9%. Outcome consisted of complete remission in 27%, incomplete remission in 32%, stable disease in 24%, deterioration in 6% and death in 5%. Conclusion Neurosarcoidosis has a heterogeneous clinical presentation and the diagnosis can be difficult because of low sensitivity of ancillary investigations. New treatments have emerged, but nevertheless one third of patients do not respond to treatment. Prospective cohort studies and RCTs on treatment are urgently needed.